1988
DOI: 10.1017/s0003356100018973
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of British Friesian, Canadian Holstein and beef breed × British Friesian steers slaughtered over a commercial range of fatness from 16-month and 24-month beef production systems 2. Carcass characteristics, and rate and efficiency of lean gain

Abstract: Link to this article: http://journals.cambridge.org/abstract_S0003356100018973How to cite this article: A. J. Kempster, G. L. Cook and J. R. Southgate (1988). Evaluation of British Friesian, Canadian Holstein and beef breed × British Friesian steers slaughtered over a commercial range of fatness from 16-month and 24month beef production systems 2. Carcass characteristics, and rate and efciency of lean gain. Animal Production, 46, pp 365-378 ABSTRACT Carcass characteristics, and the rate and efficiency of lean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
28
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 26 publications
(28 reference statements)
12
28
1
Order By: Relevance
“…Also Andersen et al (1977) found that Limousin cross young bulls from dairy cows had lower daily liveweight gains than and similar daily carcass gains as Danish Red and White young bulls. Southgate et al (1988) reported similar live growth rates for Friesian, Friesian × Hf and Friesian × Li steers in a 16-month beef system but in a 24-month system the Limousin crosses were superior.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Also Andersen et al (1977) found that Limousin cross young bulls from dairy cows had lower daily liveweight gains than and similar daily carcass gains as Danish Red and White young bulls. Southgate et al (1988) reported similar live growth rates for Friesian, Friesian × Hf and Friesian × Li steers in a 16-month beef system but in a 24-month system the Limousin crosses were superior.…”
Section: Discussionmentioning
confidence: 86%
“…Other studies have also shown that the late maturing breed type cattle have higher proportions of high value joints than early maturing breed crosses or pure dairy breeds (Keane et al, 1989Keane and More O'Ferrall, 1992). The higher lean and lower fat contents in the carcasses of the Friesian × Li than in Friesian cattle have reported Kempster et al (1988), Keane et al (1989) and Steen and Kilpatrick (1995). Furthermore, Forrest (1981) observed that the crossbred Holstein × Li steers had more lean and less fat than the purebred Holstein-Friesian steers, and similar results were reported also by Kempster et al (1976) for fat and Kempster and Jones (1971) for lean when comparing purebred Friesian and Friesian × Limousin crossbreds.…”
Section: Discussionmentioning
confidence: 96%
“…However, carcass conformation was significantly higher with the NOR compared with HF bulls. The latter observation is of major commercial importance as conformation is correlated with muscle size and distribution (Kempster et al, 1988) and suggests that carcasses of NOR bulls would yield a greater mass of lean meat per unit of carcass weight than HF bulls slaughtered at a comparable age. Furthermore, the higher carcass conformation score recorded with NOR compared with HF bulls is in line with previous studies which have reported higher carcass conformation scores with animals containing a proportion of beef genes compared with those bred solely for dairy characteristics (Kempster et al, 1988;Keane et al, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…This observation probably reflects the reduction in lean growth potential due to the increased stage of maturity of the bulls with increasing slaughter age as discussed previously. Nevertheless, the increased fat deposition at the higher slaughter age would have been expected to produce some improvement in carcass conformation, given that conformation is a visual assessment of the thickness of both muscle and fat in relation to the size of the skeleton (Kempster et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The slightly higher dressing-out percentage for bulls relative to steers has been reported in some previous studies (Geay 1978) but not in others (Hedrick et al 1969;Purchas 1990). Lower dressing-out percentages for Friesian cattle relative to their crosses with beef breeds have been reported elsewhere (Hight et al 1973;Holmes 1976;Kempster et al 1982Kempster et al , 1988Keane et al 1990;Purchas & Aungsupakorn 1993). For the MLC studies (Kempsteretal.…”
Section: Liveweight Gainmentioning
confidence: 53%